2016
DOI: 10.1111/coa.12491
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of anatomic criteria for predicting parotid tumour location

Abstract: rMasseter and tMasseter were useful as anatomic landmarks to differentiate a parotid deep lobe tumour from a superficial lobe tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 14 publications
0
20
2
Order By: Relevance
“…Kurabayashi et al first compared the FNline with the tMasseter and the tRMV in 36 cases, and showed lower accuracy (81%) and sensitivity (13%) . Previous reports showed an accuracy ranging from 63% to 85% and a sensitivity ranging from 13% to 89% . Our results showed a higher accuracy (92%) than previous studies.…”
Section: Discussioncontrasting
confidence: 65%
See 4 more Smart Citations
“…Kurabayashi et al first compared the FNline with the tMasseter and the tRMV in 36 cases, and showed lower accuracy (81%) and sensitivity (13%) . Previous reports showed an accuracy ranging from 63% to 85% and a sensitivity ranging from 13% to 89% . Our results showed a higher accuracy (92%) than previous studies.…”
Section: Discussioncontrasting
confidence: 65%
“…Among these three criteria, the tMasseter had the best performance, with an accuracy of 93% and a sensitivity of 40%. Previously reports of the tMasseter, which was proposed by Kurabayashi et al in 1993, showed an accuracy ranging from 86% to 92% and a sensitivity ranging from 44% to 63% . Despite its high accuracy, the low sensitivity made it a weak diagnostic criterion …”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations